The association of comfort and vision in soft toric contact lens wear. Issue 4 (August 2021) - Maldonado-Codina, Carole; Navascues Cornago, Maria; Read, Michael L.; Plowright, Andrew J.; Vega, Jose; Orsborn, Gary N.; Morgan, Philip B.
Abstract: Purpose: This work set out to investigate if there was an association between subjective comfort and both subjective and measured vision during the use of contemporary daily disposable soft toric contact lenses. Methods: Thirty-eight habitual soft contact lens wearers wore each of three daily disposable toric lenses for one week in a prospective, crossover, randomised, single-masked study. The following clinical measures were recorded at dispensing and follow-up visits: biomicroscopy scores, lens fitting (including rotation and rotational stability), high and low contrast visual acuity, subjective vision quality and subjective ocular surface comfort. Subjective scores were collected using 0–10 numerical grading scales. Comfort scores were analysed using a linear regression model with age, sex, visit, phase of crossover ('phase'), lens type, lens rotation, lens rotational stability, visual acuity, cylinder power and subjective vision quality as factors of interest and then refined using backward stepwise regression. Results: Thirty six participants (31.1 ± 13.5 years) completed the study. Comfort scores were found to be associated with subjective vision quality (F = 127.0 ; p < 0.0001), phase (F = 7.2; p = 0.001) and lens type (F = 4.9; p = 0.009). Greater comfort scores were observed with greater subjective vision quality scores. Visual acuity was not statistically significant in the model. Conclusion: This work suggests that symptoms of ocular discomfort may be more intense if there is also perceived visual compromise in daily disposable soft toric lenses. There was a stronger positive correlation between comfort and subjective vision quality compared with comfort and measured visual acuity.